VD_FINDINFO HC / 2014 / 115 vom 3. Dezember 2013 - VD Tribunal cantonal (2013)
HEURES DE TRAVAIL SUPPLÉMENTAIRES, DURÉE ET HORAIRE DE TRAVAIL, CONTRAT DE TRAVAIL | 321c al. 1 CO, 321c CO, 42 al. 2 CO, 42 CO